Periodic Benefit-Risk Evaluation Report: A Review of Changes - A. R. Titova; N. V. Kosyakina; T. S. Polikarpova; Yu. S. Skorodumova; V. A. Polivanov; K. V. Gorelov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
A periodic benefit-risk evaluation report (PBRER) is a retrospective evaluation document enabling marketing authorisation holders to present the results of a critical analysis of the benefit-risk ratio of a medicinal product. PBRER submission and content requirements changed with the adoption of the second edition of the Guideline on Good Pharmacovigilance Practice of the Eurasian Economic Union (EAEU GVP Guideline) in 2022.The aim of the study was to analyse the changes to the EAEU GVP Guideline requirements for the submission procedure and the content of PBRERs.The authors analysed the main changes concerning the procedure for submitting PBRERs on multi-source and well-established medicinal products, herbal and homoeopathic medicines. The authors evaluated the updated requirements for the content of PBRER sections. The analysis identified no significant changes in the aim and concept of PBRERs.The results of the analysis described in this article will help marketing authorisation holders improve the quality of PBRERs and ensure compliance with the new requirements of the EAEU GVP Guideline.